373. Development of multiplex loop-mediated isothermal amplification (LAMP) based on a microfluidic chip for detection of HSV-1 and 2 and VZV. (15th December 2022) - Ihira, Masaru; Natsuhara, Daigo; Enya, Yasuko; Higashimoto, Yuki; Kozawa, Kei; Kawamura, Yoshiki; Sugiura, Kazumitsu; Shibata, Takayuki; Yoshikawa, Tetsushi
Abstract: Background: In the era of universal varicella vaccination, point-of-care testing for herpes simplex viruses 1 and 2 (HSV-1, HSV-2) and varicella-zoster virus (VZV) is becoming more important because of the increase in the number of breakthrough varicella cases. The Loop-mediated isothermal amplification (LAMP) method is a reliable method for rapid diagnostic tests for infectious diseases. Meanwhile, microfluidics technology is revolutionary in total system miniaturization, including facile parallelization through multiplexing and process-reduced reagent volumes. It is easy to create miniaturized chips containing multiple chambers according to the needs. In this study, we sought to develop multiplex LAMP for the detection of HSV-1, HSV-2, and VZV DNA using in-house microfluidic chips. Methods: The polydimethylsiloxane-based chip consists of microfluidic channels and 5 reaction chambers. The specific primers were pre-spotted and dried in each chamber. The condition of LAMPs and each specific primer were described previously. The sensitivity of microfluidic LAMPs was confirmed using plasmids that contain the target sequences. In order to assess the reliability of clinical use, 35 swab samples (without DNA extraction) collected from patients with vesicular skin lesions were used. The result of microfluidic multiplex LAMP was compared with conventional LAMPs and real-time PCRs. Results: Detection limits of HSV-1 and 2 and VZV LAMP-based on a microfluidic chip were 500 copies per reaction. Among 35 swab samples, HSV-1, HSV-2, and VZV DNA were detected in 10 (28.6%), 4 (11.4%), and 12 (34.3%) samples, respectively. The results of microfluidic LAMPs were completely consistent with the results of conventional LAMPs. HSV-1 DNA was detected in one LAMP negative sample by real-time PCR. One HSV-1 LAMP positive sample was negative in real-time PCR. If real-time PCR was used as a standard, sensitivity of HSV-1, HSV-2, and VZV LAMPs based on microfluidic chip were 90%, 100%, and 100%, and the specificity of three methods were 96%, 100% and 100%, respectively. Conclusion: Multiplex LAMP, based on a microfluidic chip that detects three alpha herpesviruses, may be useful in laboratory diagnosis of patients with vesicular skin lesions. Disclosures: All Authors : No reported disclosures.